Mengembangkan Kredibilitas untuk Representasi Diri - Masali, Felicia; Pandrianto, Nigar (Kiwari, 2024)
One of the uses of social media is to socialise, express, find matches, and even provide education. Mico Live is a live broadcast application. This research wants to explain the communication process of hosts in the Eternite Management community to find out the self-identity built into doing live broadcasts and how hosts develop credibility. The author uses a qualitative approach with the digital ethnography method. The research data was obtained through in-depth interviews with host Mico as well as additional information from Mico's audience. This research shows the representation of Mico Live host's self-identity in live broadcasts as a model that carries an educational role. This is due to personal awareness that has previously been formed through modules, which are then constructed through real experiences. Thus, each host can develop credibility for a more positive self-representation. Salah satu kegunaan media sosial adalah menjadi ajang bersosialisasi, berekspresi, pencarian jodoh, bahkan dalam memberikan edukasi. Mico Live merupakan aplikasi siaran langsung. Penelitian ini ingin menjelaskan proses komunikasi host dalam komunitas Eternite Manajemen untuk mengetahui identitas diri yang dibangun dalam melakukan siaran langsung dan bagaimana host mengembangkan kredibilitas. Penulis menggunakan pendekatan kualitatif dengan metode etnografi digital. Data hasil penelitian diperoleh melalui wawancara yang mendalam dengan host Mico serta informasi tambahan dari penonton Mico. Penelitian ini menunjukkan representasi identitas diri host Mico Live dalam siaran langsung sebagai model yang membawa peran edukasi. Ini disebabkan kesadaran pribadi yang sebelumnya sudah dibentuk lewat modul yang kemudian dikonstruksi melalui pengalaman nyata. Dengan demikian, setiap host dapat mengembangkan kredibilitas untuk representasi diri yang lebih positif.